Instrumentalization vs Instrumentation of Microlearning in a Math Class - Enrique Mateus-Nieves; Edison Ferney Chala Castillo (AT-TA'LIM, 2021)
The study aims to innovate the teaching and learning process of mathematics with a group of elementary school students from a rural population of Colombia, where the use of information and communications technology resources, as well as internet access in limited. The teachers implement microlearning so that children learn to solve arithmetic problems. The experience is descriptive with a non-probabilistic convenience sampling, developed from the creation and application of a virtual learning object whose pedagogical strategy was the use of microlearning. The study shows that the use of information and communications technology resources assist the students to learn mathematics. It also develops the office content, skill to interpret, know and solve mathematical problems from everyday situation to students